ANALISIS KESULITAN SISWA DALAM MENGGUNAKAN EYD HURUF KAPITAL, HURUF MIRING, DAN HURUF TEBAL PADA MATA PELAJARAN BAHASA INDONESIA KELAS V DI SD NEGERI 044843 PERTUMBUNGEN TAHUN AJARAN 2021/2022 - Fenty Morina Br Sembiring; Pandapotan Tambunan; Irwansyah Irwansyah (Universitas Asahan, 2022)
This study aims to analyze students' difficulties in using EYD, and to find out the contributing factors, this research was carried out in class V SD Negeri 044843 Pertumbungen in 2021/2022. This research uses a qualitative approach and a descriptive type of research. The population and sample of this study were all students of class V SD Negeri 044843 Pertumbungen, totaling 22 people. Based on the results of the analysis of the data obtained, it is known that the ability of students to determine capital letters, italics and bold letters in the Indonesian language subject in class V SD Negeri 044843 Pertumbungen is categorized as underprivileged, because the average of the students is 46.09 and the criteria for students' ability <70 is categorized as underprivileged. Based on the test results, the percentage of students' errors in determining letters in Indonesian subjects can be seen that the most difficult thing for students to determine is determining thickness with a frequency of 19 and a percentage level of 86.36%. The cause of students having difficulty determining letters is because they do not understand or do not understand.Keywords : EYD, Indonesian Lessons, students